2005
DOI: 10.2174/1568009054863591
|View full text |Cite
|
Sign up to set email alerts
|

New Indications for Established Drugs: Combined Tumor-Stroma-Targeted Cancer Therapy with PPARγ Agonists, COX-2 Inhibitors, mTOR Antagonists and Metronomic Chemotherapy

Abstract: In search of new strategies for the treatment of cancer, the interaction between tumor and stroma attracts more and more attention. Disruption of stroma functions, e.g. angiogenesis, has evolved into a promising target for cancer therapies. Since stromal cells are genetically stable, stroma-targeted therapies seem to be less susceptible to the development of drug resistance. Several well-established drugs, which had initially been developed for other indications, also exhibit antitumor activity. Among those, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
1
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 203 publications
(260 reference statements)
1
40
1
1
Order By: Relevance
“…The novelty of our study combines metronomic chemotherapy with an anti-angiogenic agent in the clinical setting. There are few published clinical trials using such a combination, mostly phase I-II or abstracts [32][33][34][35][36][37][38][39]. In contrast to our study which showed benefit of docetaxel with thalidomide in solid tumors, Colleoni found that the addition of thalidomide to metronomic chemotherapy in advanced breast cancer patients did not improve the response rate compared to chemotherapy alone [40].…”
Section: Discussioncontrasting
confidence: 96%
“…The novelty of our study combines metronomic chemotherapy with an anti-angiogenic agent in the clinical setting. There are few published clinical trials using such a combination, mostly phase I-II or abstracts [32][33][34][35][36][37][38][39]. In contrast to our study which showed benefit of docetaxel with thalidomide in solid tumors, Colleoni found that the addition of thalidomide to metronomic chemotherapy in advanced breast cancer patients did not improve the response rate compared to chemotherapy alone [40].…”
Section: Discussioncontrasting
confidence: 96%
“…In search of new strategies for the treatment of cancer, the interaction between tumor and stroma is attracting more and more attention. Several well-established drugs (such as cyclooxygenase-2 inhibitors and mTOR antagonists), which had initially been developed for other indications, also have exhibited antitumor activity (28). Current experimental data and clinical experience suggest that these drugs (especially when administered at low repeated doses) target stroma functions as well as tumorstroma interactions and, above all, angiogenesis in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…After 84 days (four weekly administrations of 1 mg plus two monthly infusions of 4 mg of ZA), VEGF level reduction was yet statistically significant (-27.9%; 206.60 pg/mL; 95% CI: 83.45-352.13; P = 0.014). Figure 1 shows the behavior of VEGF levels at days 0,7,14,21,28, 56, and 84 after the first ZA administration.Secondary parameters. No significant differences have been recorded in platelet level, WBC count, or hemoglobin concentration before and after each ZA infusion.…”
mentioning
confidence: 99%
“…Current research data and clinical experience suggest that PPARA/G can mediate both direct antitumoral and immunomodulatory effects and a broad spectrum of stroma modulating activity including antiangiogenic, antiinflammatory, and immunoaugmentative effects [21,22]. Examples of superadditive complementation of PPARG agonists by COX2 inhibitors and metronomic chemotherapy are well-documented experimentally and in clinical trials, respectively [10,16,23].…”
Section: Introductionmentioning
confidence: 99%